A role for soluble ST2 in vascular remodeling associated with obesity in rats. - Ernesto Martínez-Martínez (Public Library of Science (PLoS), 2013)
Background The function of the Interleukin-33 (IL-33)/ST2 system has been mainly investigated on immunological aspects, but recent data suggest that this pathway plays also an important role in cardiovascular system and adipose tissue. Whereas IL-33 has been demonstrated to exert anti-inflammatory and protective effects, circulating soluble ST2 (sST2) has emerged as a prognostic biomarker in patients with myocardial infarction and heart failure. Furthermore, sST2 is increased in severe obesity, although its role in the pathogenesis of vascular remodeling associated with obesity is still not well defined. Methodology/principal findings Male Wistar rats fed standard diet (Control) or high fat diet (HFD) for 6 weeks. Aortic tunica media from diet-induced obese animals showed hypertrophy and fibrosis. The IL-33/ST2 system was spontaneously expressed in the aorta from Wistar rats. Administration of HFD in animals did not modify IL-33 expression at the transcriptional level. By contrast, HFD group showed an increase in aortic soluble sST2 and a decrease in the transmembrane isoform (ST2L) levels, resulting in decreased protective pathway activity. Aortic sST2 mRNA levels were associated with parameters showing vascular hypertrophy and fibrosis. In vitro experiments showed that primary cultured vascular smooth muscle cells (VSMCs) spontaneously expressed the IL-33/ST2 system. VSMCs stimulated with sST2 showed an increase in collagen type I, fibronectin and profibrotic factors. Conclusions This is the first study demonstrating a deleterious role for sST2 in the vascular remodeling associated with obesity. In addition, we demonstrated that sST2 may act not only as a decoy receptor by binding IL-33 and preventing ST2L, but also modulating ECM remodeling and turnover. Thus, sST2 could be a new therapeutic target to reduce vascular remodeling in the context of obesity.